Unveiling the Synergistic Potential: Bispecific Antibodies in Conjunction with Chemotherapy for Advanced Non-Small-Cell Lung Cancer Treatment - Saqib Raza Khan; Daniel Breadner (Current Oncology)
Lung cancer remains the leading cause of cancer-related mortality worldwide, with non-small-cell lung cancer (NSCLC) accounting for the majority of the cases. Despite advancements in targeted therapies and immunotherapies, many patients still rely on chemotherapy, highlighting the need for innovative treatment strategies. Bispecific antibodies (bsAbs), which feature two distinct binding sites capable of targeting different antigens, have emerged as a promising therapeutic approach, particularly in combination with chemotherapy. This review explores the scientific evolution and clinical application of bsAbs in NSCLC, focusing on their synergistic potential with chemotherapy. BsAbs, such as amivantamab, which targets EGFR and MET, have demonstrated significant efficacy in clinical trials, particularly in patients with EGFR mutations. The combination of bsAbs with chemotherapy enhances immune-mediated tumor destruction by modulating the tumor microenvironment and overcoming resistance mechanisms. Recent clinical trials have shown improved progression-free survival and overall survival when bsAbs such as amivantamab are combined with chemotherapy, underscoring their potential to transform NSCLC treatment. Many other clinical trials are underway that are evaluating newer bsAbs, such as ivonescimab, which targets PD1 and VEGF. This review also discusses ongoing clinical trials investigating various bsAbs targeting EGFR, PD-1, PD-L1, HER2, and other pathways, highlighting the future directions of bsAb-based therapies. As the field evolves, bsAbs are poised to become a cornerstone of multimodal NSCLC treatment, offering more effective and personalized therapeutic options for patients with advanced disease.